Analysis of English Learning Supervision for Certified Teachers at Yapenthom 1 Junior High School Maumere - Ephi Rusmina; Yanto Yanto; Antonius M.K. Naro (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This research aims to analyze the process of English language learning supervision for certified teachers, the problems faced by certified English teachers in the supervision process, and the impact of English language learning supervision on certified teachers. The study used a qualitative research design, with data collection methods including interviews with English teachers and the school principal. The findings revealed that the certified English teacher demonstrated strong professionalism by using interactive methods such as games, ice-breaking activities, and teaching media like laptops and projectors. The teacher also displayed effective classroom management that encouraged student participation. However, the main challenge identified was students limited English vocabulary, which hindered their learning fluency. Supervision was found to have a positive impact on improving teachers’ administrative discipline and teaching quality. It encouraged teachers to be more organized, innovative, and responsive to educational developments. The principal appreciated the English teacher’s consistency and dedication, especially in implementing improvements after supervision. Nevertheless, the study also found that the lack of a structured and continuous supervision process could reduce its effectiveness. Therefore, a balanced supervision model that is both flexible and well-structured is essential to ensure the effectiveness of Englis language learning supervision for certified teachers. This research is expected to serve as a reference for principal and policymakers in developing more effective and sustainable supervision systems.